IMPLEMENTASI MODEL PEMBELAJARAN INOVATIF DALAM PENGEMBANGAN KURIKULUM DI MTsN 1 MALUKU TENGAH - Ulfatul Muhsinah (PT. Hasba Edukasi Mandiri, 2025)
This study aims to examine the implementation of innovative learning models in curriculum development at MTsN 1 Maluku Tengah using a qualitative approach. Data collection was conducted through online interviews with a written question format, allowing respondents to provide detailed and in-depth answers. Analysis of the responses from ten teachers across various subjects revealed that the application of innovative learning models, including problem-based learning, cooperative learning, project-based learning, and the use of interactive media and technology, has a significant positive impact on the teaching and learning process. The findings indicate an increase in student enthusiasm and active engagement in a more interactive and challenging learning environment. These innovative models also contribute to the enhancement of critical thinking, creativity, and collaboration among students. However, teachers face challenges such as time constraints, infrastructure limitations, and resource availability.